Optimum Fund Allocation Strategy by Considering the Company's Assets and Liabilities - Qurrotu Aini; Dwi Susanti; Riaman Riaman (Research Collaboration Community (RCC), 2023)
Investment is essentially placing some funds at present with the expectation of future profits. The basic thing that an investor needs to know is that there is a risk that follows the profit/return. In determining the proper allocation of funds, an investor needs to consider the company's assets and liabilities. Company assets can be in the form of shares, property, and others. Meanwhile, the company's liabilities include debts and other obligations. One of the sectors whose company value has stagnated or increased during the Covid-19 Pandemic is the financial sector. Securities companies are a sub-sector of the financial sector which has a fairly strong position during the Pandemic. This research aims to determine the weight of fund allocation in each company forming the optimum portfolio and to see the effect of the company's assets and liabilities on the formation of the optimum portfolio. One of the methods used is the Lagrange Multiplier method for model formulation. The results of this study show that the optimal portfolio weight of PANS companies is 16.31% with an allocation of funds amounting to Rp163.612.976,00, the optimum portfolio weight of RELI companies is 83.003% with an allocation of funds of Rp830.029.681,00, and the optimum portfolio weight of TRIM companies is 0.636% with the allocation of funds amounting to Rp6.358.243,00. In this study, it was also found that the greater the percentage difference between the company's assets and liabilities, the greater the company's optimum portfolio weight.